Effect of different stocking density on the growth performances of white leg shrimp (Litopenaeus vannamei) and milkfish (Chanos chanos) in polyculture system - Gamal M. Samadan; Muhammad Irfan; Faisal Pitra; Muhammad Nur Findra; Supyan Supyan; Aras Syazili; Rovina Andriani (Depik, 2024)
Polyculture is a way of cultivating two or more types of organisms in the same container for the purpose of efficient use of land. The purpose of this study was to determine the effect of different stocking densities on the growth of white leg shrimp and milkfish by polyculture and to determine the stocking density that influences the growth of white shrimp and milkfish by polyculture in ponds. The study was designed using a completely randomized design (CRD), consisting of 3 treatments and 3 replications. The results showed that the specific growth rates in the three treatments, both white leg shrimp and milkfish varied. Similarly, the absolute weight growth between white leg shrimp and milkfish. Survival rate of white leg shrimp in treatment C, 85.56%, treatment B, 72.81%, and treatment A, 66.04%. While, the survival rate of milkfish in the three treatments was 100%. The feed conversion ratio in treatment A, 0.43, treatment C, 0.28, and treatment B, 0.17 grams. The different stocking densities of white leg shrimp and milkfish polycultures did not affect the absolute weight growth of white leg shrimp and their specific growth rate. However, there is an effect on the absolute weight growth of milkfishKeywords:shrimpmilkfishpolyculturestockingdensity